Forming of the system of primary documents services in agriculture in Soviet Lithuania - Julija Zinkevičienė (Knygotyra)
The article is devoted to the results of the analysis of expert evaluation of the databases that are received in our republic. These databases differ according to their value for the specialists of agriculture. The general contents of these databases do not coincide with the requirements of those specialists, but it is possible to use special themes in the agricultural information systems.